The Effect of Compensation and Work Environment on Employee Performance at PT Adira Finance Palopo Branch - Satriani, Satriani; Kusdarianto, Indra; Saharuddin, Saharuddin (Journal of Applied Business, Taxation and Economics Research, 2026)
This study aims to investigate how compensation and work environment conditions affect employee performance at PT Adira Finance, Palopo Branch. Using quantitative methods, data were obtained through a well-designed questionnaire. The study population was 50 employees at the branch. By applying the Slovin formula and random sampling techniques, we selected 50 respondents for analysis. Data management was carried out using SPSS version 25 software, which included partial checks through t-tests. The main findings indicate that compensation and work environment have a positive impact on employee performance. This study also enriches the literature with empirical evidence on the influence of these two factors on employee performance at PT Adira Finance, Palopo Branch, while providing valuable insights for company leaders to improve how to manage human resources more effectively.